2022
DOI: 10.1038/s41598-021-04354-w
|View full text |Cite
|
Sign up to set email alerts
|

Automated segmentation of articular disc of the temporomandibular joint on magnetic resonance images using deep learning

Abstract: Temporomandibular disorders are typically accompanied by a number of clinical manifestations that involve pain and dysfunction of the masticatory muscles and temporomandibular joint. The most important subgroup of articular abnormalities in patients with temporomandibular disorders includes patients with different forms of articular disc displacement and deformation. Here, we propose a fully automated articular disc detection and segmentation system to support the diagnosis of temporomandibular disorder on mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Therefore, it is imperative to include the years of experience possessed by the clinical operators annotating the training datasets to exclude the likelihood of inaccurate classifications. For context, only 40% of the investigations reported on the clinical operators' years of experience prior to data annotation 20,23,28–32,34 . From the available information, the average years of experience held by the clinical operator was 13.7 years with at least 3 years of experience observed per operator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is imperative to include the years of experience possessed by the clinical operators annotating the training datasets to exclude the likelihood of inaccurate classifications. For context, only 40% of the investigations reported on the clinical operators' years of experience prior to data annotation 20,23,28–32,34 . From the available information, the average years of experience held by the clinical operator was 13.7 years with at least 3 years of experience observed per operator.…”
Section: Discussionmentioning
confidence: 99%
“…The current review revealed several areas for improvement in the administrative handling of machine learning projects. It was seen that the majority of the funds and ethical approvals to use clinical TMJ data for deep learning were provided in South Korea (25%), 18,20,23,29,33 USA (25%) 10,22,24–26 and Japan (15%) 30,31,36 . and held by key research teams.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 10 years, there has been increasing interest in the application of deep learning to dental treatment [3][4][5][6][7][22][23][24] . Medical images are regarded as the primary input for AI applications in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…From 2015 to March 2020, the United States Food and Drug Administration approved 222 AI-equipped medical devices, including three dental devices 1) . AI research related to dentistry is actively underway [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…This preparation may be achieved by “deep mutational scanning” observing “surface antigens drifts and shifts of the pathogens in silico using artificial intelligence and machine learning.” 6 In the meanwhile, the dentists should review all existing technology, particularly radiographic, adapting and developing it further so that it not only addresses new infection control challenges, reducing the radiation dose to their patients, but also improves the quality of the display of the patient and the accompanying disease. This also means developing technologies that do not use ionising radiation, such as qualitative light-induced fluorescence for the diagnosis of early caries 37 and magnetic resonance imaging (MRI) optimally used for temporomandibular joint diseases 38 and lesions of the salivary glands and other soft-tissue of the face, jaws, and upper neck. Although MRI units are generally only sited in medical facilities, ultrasonography can be used in the dental office.…”
Section: Discussionmentioning
confidence: 99%